PATHOGENETIC THERAPY FOR ATOPIC DERMATITIS IN CHILDREN: CURRENT ISSUES - G.I. Smirnova ("Paediatrician" Publishers LLC, 2006)
The lecture presents current opinions on the problem of topical treatment of atopic dermatitis in children discussing different topical antiainflamatory drugs with and without corticosteroids. pimecrolimus 1% cream (elidel, novartis pharma, Germany) is specially emphasized among the latter. Pimecrolimus is shown to provide symptom relief and control in mild and moderate cases of atopic dermatitis, so it could become essential in preventing exacerbations and elongation of remission periods of the disease. Key words: atopic dermatitis, topical treatment, pimecrolimus 1% cream.